SINERGI INKLUSI KEUANGAN DAN LITERASI KEUANGAN DALAM EKOSISTEM DIGITAL TERHADAP KINERJA UMKM DI KOTA SURABAYA - Fredy Apritama Djunaidi; Galang Febriansyah; Ach. Royis Rizaldy; Adam Ahmad; Achmarul Fajar (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the synergy between financial inclusion and financial literacy within the digital ecosystem and its impact on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Surabaya City. The rapid development of digital financial services such as mobile banking, e-wallets, and QRIS has provided broader access for MSMEs to engage with formal financial systems. However, the utilization of these services is still not optimal due to the limited level of financial literacy among business actors. This research employs a descriptive qualitative approach using a literature review method by examining various academic journals, books, and official institutional reports. The findings indicate that financial inclusion in the digital ecosystem improves access to financing, enhances transaction efficiency, and supports market expansion for MSMEs. Meanwhile, financial literacy plays a crucial role in improving financial management capabilities, decision-making processes, and risk control (Lusardi & Mitchell, 2014). Furthermore, this study finds that the synergy between financial inclusion and financial literacy produces a more significant impact on MSME performance compared to when these variables are applied separately. MSMEs that have both access to financial services and adequate financial knowledge tend to experience improvements in income, operational efficiency, competitiveness, and business sustainability (Demirgüç-Kunt et al., 2018). In the context of Surabaya, the digital ecosystem acts as a supporting factor that strengthens this relationship. Therefore, strengthening financial literacy and expanding digital financial inclusion are essential strategies to improve MSME performance sustainably (OJK, 2023).